Implementing a Need-Adapted Stepped-Care Model for Mental Health of Refugees: Preliminary Data of the State-Funded Project “RefuKey” - Trilesnik, Beata; Altunoz, Umut; Wesolowski, Janina; Eckhoff, Leonard; Ozkan, Ibrahim; Loos, Karin; Penteker, Gisela; Graef-Calliess, Iris Tatjana (Frontiers in Psychiatry, 2019)
Introduction Refugees have shown to be a rather vulnerable population with increased psychiatric morbidity and lack of access to adequate mental health care. By expanding regional psychosocial and psychotherapeutic care structures and adapting psychiatric routine care to refugees’ needs, the state-funded project “refuKey” based in Lower Saxony, Germany pursues to ease access to mental health care and increase service quality for refugees. A stepped care treatment model along with intercultural opening of mental health care services is proposed. Methods The project is subject to a four-part evaluation study. The first part investigates the state of psychiatric routine care for refugees in Lower Saxony by requesting data from all psychiatric clinics, participating and non-participating ones, regarding the numbers of refugee patients, their diagnoses, settings of treatment etc. The second part explores experiences and work satisfaction of mental health care professionals treating refugees in refuKey cooperation clinics. The third part consists of interviews and focus group discussions with experts regarding challenges in mental health care of refugees and expectations for improvement through refuKey. The fourth part compares mental health parameters like depression, anxiety, traumatisation, somatisation, psychoticism, quality of life as well as “pathways-to-care” of refuKey-treated refugees before and after treatment and, in a follow-up, to a non-refuKey-treated refugee control group. Results RefuKey-treated refugees reported many mental health problems and estimated their mental health burden as high. The symptoms decreased significantly over the course of treatment. Mental health in the refuKey sample was strongly linked to post-migration stressors. Discussion The state of mental health care for refugees is discussed. Implications for the improvement and the need for adaptation of routine mental health care services are drawn.